Spór filologiczny wokół kazania Piotra Skargi wygłoszonego w Wilnie 9 września 1601 roku - Szymczak, Dawid (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The subject matter of this article is the episode of Skarga’s creations, concerning the argument with a protestant writer and publisher, Daniel Cramer. The conflict referred to the speech made by the Jesuit, just before the war expedition of King Sigismund III Vasa which started in Inflants. The essence of the speech was subsequently translated into German by an anonymous translator, a witness of this event. Furthermore, it was published as a maligning source against the king’s preacher. As a response, Skarga had created his own written version of the speech, in such a form in which it was originally meant to be spoken. Afterwards he compared it to the German-language translation. By juxtaposing those two texts, he wanted to show in what way the opponents, in his opinion, manipulated the written forms of the facts. In addition, his objective was to restore the basic philological processes, which was conducted during the modification of his speech.